(untitled) (Research, Society and Development, 2023)
Objective: To develop and validate the content of an e-book to disseminate the origin of the eponyms of surgical instruments. Methods: Methodological study by quantitative approach, with the development and validation of content by expert judges. A questionnaire that uses a Likert-type scale was applied, evaluating 3 blocks: objectives, structure and presentation, relevance. For this, 11 expert judges participated in the research, the calculation of CVI (Content Validity Index – in English) was stipulated at 80% to be considered validated. Results: After the elaboration and validation of the e-book entitled “The origin of surgical instruments and their inventors”, the product obtained a global CVI of 0.95 among the judges. The judges suggested improvements which were accepted and modified for the last version, which is available digitally for free. Conclusion: The product was validated by the judges, which proves to be a tool that fulfills its objective of contributing to the historical disappearance of bibliographical references of big names that contributed to the evolution of medicine.